Üniversite Öğrencilerinin Cinsel Yolla Bulaşan Hastalıklar Konusunda Bilgi ve Görüşlerinin İncelenmesi. - YAŞAR, Öznur; DİKOĞLU BULUŞ, Merve; ÖZSEZER KAYMAK, Gözde; ER GÜNERİ, Sezer (Journal of Academic Research in Nursing (JAREN), 2019)
Objective: This research was performed to determine the knowledge and opinions of students about sexually transmitted diseases (STDs). Methods: Descriptive and cross-sectional study was performed with 250 out of 327 female students staying in girls'dormitory in a special school for girls in Balikesir province, and who volunteered to participate in the study during the academic year of 2014-2015 between 06 and 15 March 2015.The participants were not students of a health high school or medical school. A questionnaire consisting of 21 questions was used as data collection tool. Statistical Package for Social Sciences for Windows 16.0 was used in computer program with descriptive analysis including arithmetic mean, percentiles and Pearson chi-square test. Resuts: The mean age of the students was 20.94 (± 1.82) years, and 70,8%, of them lived in metropolitan city. A 44.4% of the participants said that were not talking about sexuality in the family, while 56% of them said that they were against any kind of sexual relations before marriage. Besides, 66% of them had knowledge about sexual health and reproductive health, and television, book, magazine were reported as sources of information by 24% of the students. The indicated percentages of the students stated that having more than one sexual partner (77.2%), liivng with a prostitute, (61%), and being a drug addict (9.6%) as risk factors for the transmission of STDs. The 96% of the students stated that STDs were transmitted via blood, and 95% of them indicated that these diseases would cause health problems. While 71.2% of the students stated that could use condoms to be protected from STDs. A significant difference among students as for the living place of the participants before they entered in the university, and talking about sexuality in the family was not detcted. Conclusion: In the study, it was determined that university students had information needs about STD symptoms and risk factors. It has come to the conclusion that necessary training should be done before young people exhibit risky behavior in the early period.